Nanosystems for Improved Targeted Therapies in Melanoma - Beiu, Cristina (J Clin Med, 2020)
Melanoma is one of the most aggressive forms of skin cancer, with limited therapeutic options. Since its incidence has been rapidly rising in recent years, the study of new targeted therapeutic strategies has increased. The implication of nanoscience in the development of alternative targeted therapies for melanoma has multiple benefits and could significantly improve the outcome of melanoma patients. In this paper, we review the most recent progress in the field of targeted therapies, emphasizing the impact of nanoscale materials on the targeting and controlled release of anti-tumor drugs. The applications of nanomedicine in the management of melanoma are extensive and refer to sentinel lymph node mapping, chemotherapy, and RNA interference; each of these applications harboring the potential to develop efficient and personalized diagnostic techniques and therapies. Further research, especially in clinical trials, is needed to establish whether fighting melanoma on the nanoscale level represents the key to reaching a critical inflection point in mankind’s battle with metastatic melanoma.